2001
DOI: 10.1021/ed078p981
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Structures in General Chemistry: Agreement between Electron Density Calculations and Lewis Structures

Abstract: How to draw the most appropriate Lewis structure for molecules and ions in which nonmetal atoms beyond the second period are bonded to a terminal oxygen atom has been the subject of considerable debate. Recently there has been a shift toward satisfying the octet rule even if formal charges remain on the structure. In this work, the internuclear electron densities of a series of X-O bonds (where X = P, S, or Cl) have been calculated using quantum mechanics and compared to Lewis structures for which the formal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…There are many articles in this Journal and elsewhere which propose methods for teaching the drawing of Lewis structures starting from an assumed or known molecular connectivity. A common approach is to start with the known molecular connectivity and to add bonds of different orders between the atoms using the valence electrons from all of the atoms in electron pair bonds to try to achieve an octet or some other number of electrons in the valence shell of each atom and finally apply a formula to each atom to see if there are any formal charges which should be added. Some authors advocate the use of up to seven steps in the process of producing a structure …”
Section: Lack Of a Systematic Approach To Drawing Lewis Structuresmentioning
confidence: 99%
“…There are many articles in this Journal and elsewhere which propose methods for teaching the drawing of Lewis structures starting from an assumed or known molecular connectivity. A common approach is to start with the known molecular connectivity and to add bonds of different orders between the atoms using the valence electrons from all of the atoms in electron pair bonds to try to achieve an octet or some other number of electrons in the valence shell of each atom and finally apply a formula to each atom to see if there are any formal charges which should be added. Some authors advocate the use of up to seven steps in the process of producing a structure …”
Section: Lack Of a Systematic Approach To Drawing Lewis Structuresmentioning
confidence: 99%
“…For well over 40 years, reports in this Journal have described alternative instructional strategies intended to help students better develop their abilities to draw and manipulate Lewis structures. The impact of these strategies, however, is questionable as our previous research has shown that even fairly simple structure-creation tasks can still be quite challenging for students . In trying to engage in these tasks, which often required skills, knowledge, and experiences that they had yet to develop, students frequently relied on a set of homegrown rules and heuristics .…”
Section: Teaching and Learning Of Lewis Structuresmentioning
confidence: 99%
“…Unfortunately, many students simply apply rule-based methods to drawing Lewis structures and do not learn to interpret their purpose and function. Such students have difficulty with the complex interpretation involved in connecting structure to physical properties. Reports advocating new and improved “step-by-step” approaches to drawing Lewis structures may support students in learning the mechanics of Lewis structure drawing, but these approaches do not address the issue of interpretation. A version of writing-to-learn based on directed reading and writing responds to and builds on the constructivist model of learning advocated by Cooper (2010), who claims that a new approach is needed (ref , p 873):It is crucial that we rethink how to best develop and reinforce these skills in a framework that allows students to learn in a meaningful way so that they can develop and appreciate the relationship between structure and function.The literature of writing-to-learn shows that asking students to explain, reflect on, and elaborate in writing the concepts they study in science classes fosters meaningful learning. …”
mentioning
confidence: 99%